Photoluminescence test structure of active material and preparation method of photoluminescence test structure

By inserting an interface layer between the buffer layer and the material under test, the band structure is changed, which solves the double-peak interference problem in the photoluminescence test of aluminum-containing quaternary compound materials, realizes single-peak detection in the photoluminescence test, and improves the accuracy.

CN120870066APending Publication Date: 2025-10-31VERTILITE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511015257.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-23
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

In photoluminescence testing, aluminum-containing quaternary compound materials exhibit double-peak interference, which affects the determination of the true peak position and leads to inaccurate determination of the emission wavelength.

Method used

An interface layer is inserted between the buffer layer and the test material layer. There is a conduction band barrier between the interface layer and the buffer layer, and a valence band barrier between the interface layer and the test material layer. By changing the band structure through the interface layer, electrons and holes are confined in the conduction band and valence band, respectively, ensuring that the photoluminescence wavelength is a single peak.

Benefits of technology

This method enables single-peak detection in photoluminescence testing, improving the accuracy of detecting the true peak position of the material under test and avoiding the problem of double-peak interference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120870066A_ABST
    Figure CN120870066A_ABST
Patent Text Reader

Abstract

The invention discloses a photoluminescence test structure of an active material and a preparation method of the photoluminescence test structure, and the photoluminescence test structure comprises a substrate, a buffer layer, at least one interface layer, a to-be-tested material layer and a covering layer which are sequentially stacked, a conduction band potential barrier is arranged between the at least one interface layer and the buffer layer, and a valence band potential barrier is arranged between the at least one interface layer and the to-be-tested material layer. According to the photoluminescence testing structure of the active material and the preparation method of the photoluminescence testing structure, single-peak testing of PL is achieved, and the detection accuracy of the real peak position of the to-be-tested material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor technology, and in particular to a photoluminescence testing structure for active materials and its preparation method. Background Technology

[0002] In laser structures, the active layer is typically positioned between two mirrors and contains one or more quantum wells. In recent years, aluminum-containing quaternary compounds, such as indium aluminum gallium arsenide (IAA), have exhibited photoluminescence wavelengths ranging from 1.63 to 0.85 μm, covering the low-loss (1.55 μm) and low-dispersion (1.3 μm) windows of silica optical fibers. Therefore, the use of aluminum-containing quaternary compounds as quantum wells in lasers has attracted widespread research and application.

[0003] When aluminum-containing quaternary compounds, such as indium aluminum gallium arsenide, are prepared as active materials, double-peak interference occurs at some emission wavelengths when measuring their photoluminescence (PL) wavelengths. This affects the determination of the true peak position of the active material and is not conducive to determining the emission wavelength of the active material. Summary of the Invention

[0004] This invention provides a photoluminescence testing structure for active materials and its preparation method, enabling single-peak testing of photoluminescence (PL) and improving the accuracy of detecting the true peak position of the material under test.

[0005] In a first aspect, embodiments of the present invention provide a photoluminescence testing structure for an active material, comprising: a substrate, a buffer layer, at least one interface layer, a material to be tested layer, and a cover layer, which are stacked sequentially.

[0006] Wherein, there is a conduction band barrier between the at least one interface layer and the buffer layer, and there is a valence band barrier between the at least one interface layer and the material to be tested layer.

[0007] Optionally, the substrate, the buffer layer, and the capping layer all comprise indium phosphide; the at least one interface layer comprises indium aluminum arsenide.

[0008] Optionally, the thickness of the interface layer is greater than 2 nm.

[0009] Optionally, the test material layer includes an Al-containing quaternary compound.

[0010] Optionally, the quaternary compound includes indium aluminum gallium arsenide.

[0011] Optionally, the thickness of the material layer to be tested is greater than 20 nm.

[0012] Secondly, embodiments of the present invention provide a method for preparing a photoluminescence testing structure of an active material, comprising:

[0013] Provide a substrate, and place the substrate in the reaction chamber;

[0014] A buffer layer is formed on the substrate;

[0015] At least one interface layer is formed on the side of the buffer layer away from the substrate; wherein, there is a conduction band barrier between the at least one interface layer and the buffer layer, and there is a valence band barrier between the at least one interface layer and the material to be tested layer;

[0016] A test material layer is formed on the side of the at least one interface layer away from the substrate;

[0017] A cover layer is formed on the side of the material layer to be tested away from the substrate.

[0018] Optionally, the substrate, the buffer layer, and the capping layer all comprise indium phosphide; the at least one interface layer comprises indium aluminum arsenide.

[0019] After forming the buffer layer on the substrate, the method further includes:

[0020] Phosphorus gaseous material is continuously introduced into the reaction chamber for a first preset time;

[0021] Stop introducing the phosphorus gaseous material and continue purging the reaction chamber for a second preset time.

[0022] Optionally, after forming the test material layer on the side of the at least one interface layer away from the substrate, the process includes:

[0023] Arsenic gaseous material is continuously introduced into the reaction chamber for a third preset time;

[0024] Stop introducing the arsenic gaseous material and continue purging the reaction chamber for a fourth preset time.

[0025] Optionally, the range of the first preset time and the third preset time is 0-60 seconds;

[0026] The second and fourth preset times are in the range of 0.5-1200 seconds.

[0027] The technical solution provided by this invention involves disposing at least one interface layer between a buffer layer and a material under test (TUT) layer. This creates a conduction band barrier between the interface layer and the buffer layer, and a valence band barrier between the interface layer and the TUT layer. By altering the band structure of the adjacent buffer layer and TUT layer through the interface layer, electron-hole pairs are generated in the TUT layer under the excitation of excitation light. The electrons and holes are confined in the conduction band and valence band of the TUT layer, respectively. Since the band gap width of the TUT layer is fixed, when an electron transitions from the conduction band back to the valence band and recombines with a hole, it releases light of a specific wavelength. Therefore, the detected PL peak exhibits a single peak, thus avoiding the problem of double peaks in the emission wavelength and improving the detection accuracy of the true peak position of the TUT layer. Attached Figure Description

[0028] Figures 1-4 These are schematic diagrams showing the wavelengths of PL testing for active materials at PL wavelengths of 1150nm, 1010nm, 960nm, and 860nm, respectively.

[0029] Figure 5 This invention provides a schematic diagram of a photoluminescence testing structure for an active material, as shown in the embodiment of the invention.

[0030] Figure 6 This invention provides a schematic diagram of the wavelength curve for PL peak testing.

[0031] Figure 7 This invention provides another schematic diagram of the wavelength curve for PL peak testing.

[0032] Figure 8 This is a schematic diagram of a band structure provided in an embodiment of the present invention;

[0033] Figure 9 This is a schematic flowchart illustrating a method for preparing a photoluminescence testing structure of an active material according to an embodiment of the present invention.

[0034] Figure 10 A schematic flowchart illustrating a method for preparing a photoluminescence testing structure of an active material, as provided in this embodiment of the invention;

[0035] Figure 11 This is a schematic diagram of the wavelength curve for another PL peak test provided in an embodiment of the present invention. Detailed Implementation

[0036] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0037] In recent years, the photoluminescence wavelength range of aluminum-containing quaternary compounds, such as indium aluminum gallium arsenide (InAlGaAs), has been observed to be between 1.63 and 0.85 μm, covering the low-loss (1.55 μm) and low-dispersion (1.3 μm) windows of silica optical fibers. Therefore, the use of aluminum-containing quaternary compounds as quantum wells for lasers has attracted widespread research and application.

[0038] When aluminum-containing quaternary compounds, such as InAlGaAs, are used as active materials, double-peak interference can occur when measuring specific PL wavelengths after preparation. Figures 1-4 The diagrams show the wavelengths for PL testing of active materials at PL wavelengths of 1150 nm, 1010 nm, 960 nm, and 860 nm, respectively. (See attached diagram.) Figures 1-4 For active materials with a PL wavelength of 1150 nm, the corresponding measured PL behavior is a single peak (the main peak corresponds to a wavelength of 1154 nm, and the half-peak wavelengths are 1114.4 nm and 1176.9 nm, with a half-peak broadening of 62.5 nm). For active materials with a PL wavelength of 1010 nm, the corresponding measured PL behavior is a double peak (the main peak corresponds to a wavelength of 1010.2 nm, and the half-peak wavelengths are 974.2 nm and 1133.8 nm, with a half-peak broadening of 159.7 nm). According to... Figures 1-4 It can be seen that as the PL wavelength of the active material decreases, the measured PL peak gradually exhibits a double peak, until the peak disappears when the PL wavelength of the active material reaches 860nm, leaving only the substrate peak. The interference of the double peak affects the determination of the true peak position of the active material, making it difficult to ascertain the emission wavelength.

[0039] In view of this, Figure 5 This is a schematic diagram of a photoluminescence testing structure for an active material provided in an embodiment of the present invention. See also... Figure 5 It includes: a substrate 110, a buffer layer 120, at least one interface layer 130, a test material layer 140 and a cover layer 150, which are stacked in sequence.

[0040] This embodiment of the photoluminescence test structure is used to test the photoluminescence wavelength of the material under test (TUT) layer 140. The substrate 110 forms the basis of the overall structure, and other structures are grown on the substrate 110. For example, the substrate 110 can be a semiconductor substrate, such as an indium phosphide (InP) substrate 110. A buffer layer 120 serves as an intermediate layer between the substrate 110 and at least one interface layer 130, used to smooth the rough surface of the substrate after deoxidation, thereby improving the interface characteristics between the substrate 110 and at least one interface layer 130, and enhancing the stability and performance of the overall structure. The buffer layer 120 can be an InP buffer layer 120. At least one interface layer 130 is disposed between the buffer layer 120 and the TUT layer 140. In some embodiments, if the buffer layer 120 is not provided, at least one interface layer 130 can be disposed between the substrate 110 and the TUT layer 140. At least one interface layer 130 is used to change the band structure of the adjacent buffer layer 120 and the material under test layer 140, so that there is a conduction band barrier between the at least one interface layer 130 and the buffer layer 120, and a valence band barrier between the at least one interface layer 130 and the material under test layer 140. For example, the interface layer 130 may include indium aluminum arsenide (InAlAs). By altering the band structure of the adjacent buffer layer 120 and the test material layer 140 through the interface layer 130, electron-hole pairs are generated in the test material layer 140 under the excitation of excitation light. Since there is a conduction band barrier between at least one interface layer 130 and the buffer layer 120, and a valence band barrier between at least one interface layer 130 and the test material layer 140, electrons are confined in the conduction band of the test material layer 140, and holes are confined in the valence band of the test material layer 140. The band gap width of the test material layer 140 is fixed. When electrons jump from the conduction band back to the valence band and recombine with holes, they release light of a specific wavelength. Therefore, the detected PL peak is a single peak, thus avoiding the problem of double peaks in the emission wavelength and improving the detection accuracy of the true peak position of the test material.

[0041] Optionally, the substrate 110, buffer layer 120, and capping layer 150 all comprise indium phosphide (InP); at least one interface layer 130 comprises indium aluminum arsenide (InAlAs). The substrate 110 forms the basis of the overall structure. The buffer layer 120, at least one interface layer 130, the material under test layer 140, and the capping layer 150 can be prepared on the substrate 110 by metal-organic chemical vapor deposition (MOCVD) or molecular beam epitaxy (MBE). For example, the substrate 110 can be a semiconductor substrate 110, such as an indium phosphide (InP) substrate 110.

[0042] The test material layer 140 is an active material, which can be an aluminum-containing quaternary compound, such as indium aluminum gallium arsenide (InAlGaAs). The chemical formula of indium aluminum gallium arsenide can be represented as In... x Al y Ga 1-x-y As, the material composition of indium aluminum gallium arsenide has two variables, x and y, which together determine the emission wavelength and lattice constant of the material.

[0043] In this embodiment of the invention, InAlGaAs with a PL wavelength of 1000nm is used as the test object. Figure 6 This invention provides a schematic diagram of the wavelength curve for PL peak testing, as shown in the embodiment of the invention. Figure 6 There is no interface layer 130 between the buffer layer 120 and the test material layer 140. In this test structure, the substrate 110, buffer layer 120, test material layer 140 and cover layer 150 are stacked in sequence. For InAlGaAs with 0 mismatch and a PL wavelength of 1000nm, the corresponding test PL wavelength shows a double peak (the main peak corresponds to a wavelength of 1002.1nm, and the half-wave peak wavelengths are 976.1nm and 1020.0nm, respectively, with a half-wave peak broadening of 43.9nm). The test results will be affected by the double peak.

[0044] Figure 7 A schematic diagram of the wavelength curve for PL peak testing is provided for another embodiment of the present invention. See [link to diagram]. Figure 7 In this test structure, a substrate 110, a buffer layer 120, at least one interface layer 130, a test material layer 140, and a cover layer 150 are stacked in sequence. At least one interface layer 130 is inserted between the buffer layer 120 and the test material layer 140 to change the band structure of the adjacent buffer layer 120 and the test material layer. Figure 8 This is a schematic diagram of a band structure provided in an embodiment of the present invention, combined with... Figure 5 See Figure 8 There is a conduction band barrier between the InAlAs interface layer 130 and the InP buffer layer 120, and a valence band barrier between the InAlAs interface layer 130 and the InAlGaAs test material layer 140. Under the excitation of excitation light, electron-hole pairs are generated in the test material layer 140. Electrons are confined in the conduction band of the test material layer 140, and holes are confined in the valence band of the test material layer 140. The band gap width of the test material layer 140 is fixed. When electrons jump from the conduction band back to the valence band and recombine with holes, they release light of a specific wavelength. Therefore, the detected PL peak appears as a single peak, such as... Figure 7 As shown, the corresponding test PL wavelength exhibits a single peak (the wavelength corresponding to the single peak is 1000.5nm, the half-peak wavelengths are 972.8nm and 1017.8nm respectively, and the half-peak broadening is 45nm).

[0045] Based on the above embodiments, optionally, the interface layer 130 needs to be of a certain thickness. If the interface layer 130 is too thin, it cannot provide sufficient barrier confinement. Therefore, in this embodiment of the invention, the thickness of the interface layer 130 is greater than 2 nm. For example, the thickness of the interface layer 130 can be 2 nm, 5 nm, 8 nm, or 10 nm, etc. Optionally, the thickness of the test material layer 140 is greater than 20 nm to ensure the luminescence intensity of the test material layer 140 under excited light, which is beneficial for PL testing.

[0046] Figure 9 This is a schematic flowchart illustrating a method for preparing a photoluminescence testing structure of an active material according to an embodiment of the present invention. (See attached diagram.) Figure 9 ,include:

[0047] S110: Provide a substrate 110, place the substrate 110 in the reaction chamber, pre-treat the substrate 110, for example, by heating the reaction chamber to the required temperature, and introducing a suitable carrier gas, such as hydrogen or nitrogen. The substrate 110 forms the basis of the overall structure, and other structures are grown on the substrate 110. For example, the substrate 110 can be a semiconductor substrate 110, such as an indium phosphide (InP) substrate 110.

[0048] S120, A buffer layer 120 is formed on the substrate 110;

[0049] Specifically, the component materials of the buffer layer 120 are introduced into the reaction chamber via a gas feeding system, and the buffer layer 120 is grown on the substrate 110. For example, the buffer layer 120 can be an InP buffer layer 120, and its component materials can include indium vapor phase materials and phosphorus vapor phase materials, etc. The thickness of the buffer layer 120 can be 200 nm. The buffer layer 120 serves as an intermediate layer between the substrate 110 and at least one interface layer 130, used to smooth the rough surface of the substrate after deoxidation, thereby improving the interface characteristics between the substrate 110 and at least one interface layer 130, and enhancing the stability and performance of the overall structure.

[0050] S130, at least one interface layer 130 is formed on the side of the buffer layer 120 away from the substrate 110; wherein, at least one interface layer 130 has a conduction band barrier between it and the buffer layer 120, and at least one interface layer 130 has a valence band barrier between it and the material layer 140 to be tested.

[0051] Specifically, the component material of the interface layer 130 is introduced into the reaction chamber via a gas feed system, and at least one interface layer 130 is grown on the buffer layer 120. For example, the interface layer 130 can be an InAlAs interface layer 130, and the component material includes indium vapor material, aluminum vapor material, and arsenic vapor material, etc. The thickness of the interface layer 130 is greater than 2 nm. At least one interface layer 130 is used to modify the band structure of the adjacent buffer layer 120 and the test material layer 140, so that there is a conduction band barrier between the at least one interface layer 130 and the buffer layer 120, and a valence band barrier between the at least one interface layer 130 and the test material layer 140.

[0052] S140: A test material layer 140 is formed on the side of at least one interface layer 130 away from the substrate 110. The component materials of the test material layer 140 are introduced into the reaction chamber via a gas feed system, and the test material layer 140 is grown on the interface layer 130. For example, the test material layer 140 can be an InAlGaAs test material layer 140, and the component materials include indium vapor material, aluminum vapor material, gallium vapor material, and arsenic vapor material, etc. The thickness of the test material layer 140 is greater than 20 nm.

[0053] S150, A capping layer 150 is formed on the side of the material layer 140 away from the substrate 110.

[0054] Figure 10 A schematic flowchart illustrating another method for preparing a photoluminescence testing structure using an active material, as provided in this embodiment of the invention, is shown below. Figure 10 ,include:

[0055] S210. A substrate 110 is provided and placed in the reaction chamber. The substrate 110 is placed in the reaction chamber and pretreated, for example, by heating the reaction chamber to the required temperature and introducing a suitable carrier gas, such as hydrogen or nitrogen. The substrate 110 forms the basis of the overall structure, and other structures are grown on the substrate 110. For example, the substrate 110 can be a semiconductor substrate, such as an indium phosphide (InP) substrate 110.

[0056] S220, A buffer layer 120 is formed on the substrate 110; wherein, the buffer layer 120 may be an InP buffer layer 120.

[0057] Specifically, the component materials of the buffer layer 120 (such as indium vapor material and phosphorus vapor material) are introduced into the reaction chamber through a gas feeding system, and the buffer layer 120 is grown on the substrate 110. For example, the thickness of the buffer layer 120 can be 200 nm. The buffer layer 120 serves as an intermediate layer between the substrate 110 and at least one interface layer 130, smoothing the rough surface of the substrate after deoxidation, thereby improving the interfacial properties between the substrate 110 and at least one interface layer 130, and enhancing the stability and performance of the overall structure.

[0058] S230. First, stop the flow of indium vapor material, then continuously flow phosphorus vapor material into the reaction chamber for a first preset time. During this time, the phosphorus vapor material can protect the buffer layer 120. For example, the range of the first preset time is 0-60 seconds. The selection of the first preset time depends on the difference in growth temperature between the buffer layer and the interface layer. If the difference is large, a longer temperature change and stabilization time is required, then the first preset time is longer; otherwise, it is shorter.

[0059] S240. Stop introducing phosphorus gaseous material and continue purging the reaction chamber for a second preset time. For example, the second preset time ranges from 0.5 to 1200 seconds. The second preset time can be selected based on the flow rate of the gaseous material; for example, a faster flow rate allows for a shorter time, and a slower flow rate allows for a longer time. Purging the reaction chamber removes any residual phosphorus gaseous material, preventing the formation of an InAlGaAsP impurity layer when As and P mix during the growth transition between the InP buffer layer 120 and the InAlGaAs test material layer 140. This would result in additional impurity peaks in the PL test results, affecting the accuracy of the test.

[0060] S250. Arsenic gaseous material is continuously introduced into the reaction chamber for a fifth preset time. This pre-introduction of arsenic gaseous material before the growth of interface layer 130 ensures a more stable As flow rate and more uniform material quality during the subsequent growth of interface layer 130. For example, the fifth preset time ranges from 0.1 to 60 seconds. The fifth preset time can be selected based on the flow rate of the gaseous material; for example, a faster flow rate allows for a shorter introductory time, while a slower flow rate allows for a longer introductory time.

[0061] S260, at least one interface layer 130 is formed on the side of the buffer layer 120 away from the substrate 110; wherein, at least one interface layer 130 has a conduction band barrier between it and the buffer layer 120, and at least one interface layer 130 has a valence band barrier between it and the material layer 140 to be tested.

[0062] Specifically, the component materials of the interface layer 130 (such as indium vapor material, aluminum vapor material, and arsenic vapor material) are introduced into the reaction chamber via a gas feed system, and at least one interface layer 130 is grown on the buffer layer 120. For example, the thickness of the interface layer 130 is greater than 2 nm. The at least one interface layer 130 is used to modify the band structure of the adjacent buffer layer 120 and the test material layer 140, such that there is a conduction band barrier between the at least one interface layer 130 and the buffer layer 120, and a valence band barrier between the at least one interface layer 130 and the test material layer 140. For example, the interface layer 130 may include indium aluminum arsenide (InAlAs).

[0063] S270, a test material layer 140 is formed on the side of at least one interface layer 130 away from the substrate 110. Component materials (such as indium vapor material, aluminum vapor material, gallium vapor material, and arsenic vapor material) of the test material layer 140 are introduced into the reaction chamber via a gas feed system, and the test material layer 140 is grown on the interface layer 130. For example, the thickness of the test material layer 140 is greater than 20 nm.

[0064] S280. Stop introducing indium and gallium, and aluminum vapor phase material. Continuously introduce arsenic vapor phase material into the reaction chamber for a third preset time. During this time, the arsenic vapor phase material can protect the test material layer 140. For example, the range of the third preset time is 0-60 seconds. The selection of the third preset time depends on the difference in growth temperature between the test material and the capping layer. If the difference is large, requiring a long temperature change and stabilization time, then the first preset time is long; otherwise, it is short.

[0065] S290. Stop introducing arsenic gaseous material and continue purging the reaction chamber for a fourth preset time. For example, the fourth preset time ranges from 0.5 to 1200 seconds. The fourth preset time can be selected based on the flow rate of the gaseous material; for example, a faster flow rate allows for a shorter time, and a slower flow rate allows for a longer time. Purging the reaction chamber removes any residual arsenic gaseous material, preventing the formation of an InAlGaAsP impurity layer during the growth transition between the capping layer 150 and the test material layer 140. This would result in additional impurity peaks in the PL test results, affecting the accuracy of the test.

[0066] S300. Continuously introduce phosphorus gaseous material into the reaction chamber for a sixth preset time. Pre-introducing phosphorus gaseous material before the growth of the capping layer 150 ensures a more stable P flow rate and more uniform material growth during the subsequent growth of the capping layer 150. For example, the sixth preset time ranges from 0.1 to 60 seconds. The sixth preset time can be selected based on the flow rate of the gaseous material; for example, a faster flow rate allows for a shorter introductory time, and a slower flow rate allows for a longer introductory time.

[0067] S310. A capping layer 150 is formed on the side of the material layer 140 away from the substrate 110. The capping layer 150 can be an InP layer.

[0068] Based on the above preparation process, the reaction chamber is purged before the interface layer 130 and the capping layer 150 are generated to remove the residual phosphorus and arsenic gaseous materials in the reaction chamber. This avoids the formation of an InAlGaAsP interface layer when As and P are mixed during the subsequent growth process of the InP capping layer 150 and the InAlGaAs test material layer 140, which would cause additional impurity peaks in the PL test and affect the accuracy of the test.

[0069] For example, Figure 11 A schematic diagram of the wavelength curve for another PL peak test provided in this embodiment of the invention is shown below. Figure 11 Using indium aluminum gallium arsenide (InAlGaAs) with a mismatch of -5000ppm and a photoluminescence (PL) wavelength of 1000nm as the test material, the figures show the PL test wavelength curves without the interface layer 130 (blue curve), with the interface layer 130 added but not purge-optimized (red curve), and with the interface layer 130 added and purge-optimized (yellow curve). As can be seen from the figures, when no InAlAs interface layer 130 is inserted between the InP buffer layer 120 and the InAlGaAs test material layer 140, the PL peak exhibits a double peak with broadened peak positions, making it impossible to accurately calibrate the PL wavelength. However, when a 10nm InAlAs interface layer 130 is inserted between the InP buffer layer 120 and the InAlGaAs test material layer 140, but the purge interface optimization steps S230 and S280 are not performed during the growth process, the PL peak exhibits a single peak, but there are bulging-type impurity peaks near 1050nm. For the 10nm InAlAs interface layer 130 inserted between the InP buffer layer 120 and the InAlGaAs material layer, and after performing the purging interface optimization in steps S230 and S280 during the growth process, the bulge near 1050nm decreased significantly, which better meets the test requirements of PL single peak.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A photoluminescence testing structure for an active material, characterized in that, include: The substrate, buffer layer, at least one interface layer, test material layer, and cover layer are stacked in sequence. Wherein, there is a conduction band barrier between the at least one interface layer and the buffer layer, and there is a valence band barrier between the at least one interface layer and the material to be tested layer.

2. The photoluminescence testing structure for active materials according to claim 1, characterized in that, The substrate, the buffer layer, and the capping layer all comprise indium phosphide; the at least one interface layer comprises indium aluminum arsenide.

3. The photoluminescence testing structure for active materials according to any one of claims 1-2, characterized in that, The thickness of the interface layer is greater than 2 nm.

4. The photoluminescence testing structure for active materials according to claim 3, characterized in that, The material layer to be tested includes an Al-containing quaternary compound.

5. The photoluminescence testing structure for active materials according to claim 4, characterized in that, The quaternary compound includes indium aluminum gallium arsenide.

6. The photoluminescence testing structure for active materials according to any one of claims 4-5, characterized in that, The thickness of the material layer to be tested is greater than 20 nm.

7. A method for preparing a photoluminescence testing structure of an active material, characterized in that, include: Provide a substrate, and place the substrate in the reaction chamber; A buffer layer is formed on the substrate; At least one interface layer is formed on the side of the buffer layer away from the substrate; wherein, there is a conduction band barrier between the at least one interface layer and the buffer layer, and there is a valence band barrier between the at least one interface layer and the material to be tested layer; A test material layer is formed on the side of the at least one interface layer away from the substrate; A cover layer is formed on the side of the material layer to be tested away from the substrate.

8. The method for preparing the photoluminescence testing structure of the active material according to claim 7, characterized in that, The substrate, the buffer layer, and the capping layer all comprise indium phosphide; the at least one interface layer comprises indium aluminum arsenide. After forming the buffer layer on the substrate, the method further includes: Phosphorus gaseous material is continuously introduced into the reaction chamber for a first preset time; Stop introducing the phosphorus gaseous material and continue purging the reaction chamber for a second preset time.

9. The method for preparing the photoluminescence testing structure of the active material according to claim 8, characterized in that, After forming the test material layer on the side of the at least one interface layer away from the substrate, the process includes: Arsenic gaseous material is continuously introduced into the reaction chamber for a third preset time; Stop introducing the arsenic gaseous material and continue purging the reaction chamber for a fourth preset time.

10. The method for preparing the photoluminescence testing structure of the active material according to claim 9, characterized in that, The first preset time and the third preset time are in the range of 0-60 seconds; The second and fourth preset times are in the range of 0.5-1200 seconds.